1996
DOI: 10.1007/s004649900166
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a pneumoperitoneum on the peritoneal implantation of free intraperitoneal colon cancer cells

Abstract: The presence of a pneumoperitoneum does not enhance the implantation of free intraperitoneal malignant colon cancer cells in the rat, but the presence of a "port" may lead to abdominal-wall metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 0 publications
3
51
0
2
Order By: Relevance
“…Work by Bouvy et al 33,34 using both cell suspension and solid tumor models achieved similar results. In contrast, the results of Hubens and Eyskens 35 showed no difference in the rate intraperitoneal tumor growth between anesthetic controls and CO 2 insufflation. They scored peritoneal involvement with use of a scale described by Eggermont et al 36 intraperitoneal involvement on the basis of visual inspection and does not differentiate between tumor growth within the omentum and involvement of the parietal peritoneum.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Work by Bouvy et al 33,34 using both cell suspension and solid tumor models achieved similar results. In contrast, the results of Hubens and Eyskens 35 showed no difference in the rate intraperitoneal tumor growth between anesthetic controls and CO 2 insufflation. They scored peritoneal involvement with use of a scale described by Eggermont et al 36 intraperitoneal involvement on the basis of visual inspection and does not differentiate between tumor growth within the omentum and involvement of the parietal peritoneum.…”
Section: Discussionmentioning
confidence: 74%
“…38 However, studies generally demonstrate that this effect is less with laparoscopy. [32][33][34][35]39 These studies have examined the effects of laparoscopy on tumor growth at a site remote from the peritoneal cavity, such as the animal's flank, and may help to explain some of the differences between their findings and our study.…”
Section: Discussionmentioning
confidence: 90%
“…Several authors have hypothesized that the practice of insuffl ating CO 2 into the peritoneal cavity causes cell aerosolization and may promote tumor cell shedding [5][6][7][8]. A higher probability of tumor growth on the peritoneum has been associated with gas laparoscopy as opposed to gasless laparoscopy procedures [7,8]. In the case of our patient, we suggest that microscopic endometriosis or otherwise undetected endometrial tissue, disseminated to the trocar site during laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 68%
“…It has also been suggested that localized tissue ischemia renders that tissue conductive to implantation [6]. Several authors have hypothesized that the practice of insuffl ating CO 2 into the peritoneal cavity causes cell aerosolization and may promote tumor cell shedding [5][6][7][8]. A higher probability of tumor growth on the peritoneum has been associated with gas laparoscopy as opposed to gasless laparoscopy procedures [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Имеются многочисленные публикации, объяс-няющие высокую частоту рецидивирования после лапароскопических операций по поводу РЯ повы-шенным давлением газа в брюшной полости, негер-метичностью установленных троакаров, возможным негативным влиянием самого углекислого газа, труд-ностями соблюдения правил абластики в ходе вме-шательства [9][10][11]. Все эти негативные моменты на-шли подтверждение и в нашем исследовании.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified